Periprocedural antiplatelet management in cardiac patients undergoing dental extraction: A case report and review of literature - Ajay Agarwal; Osama Hallak; Tanjeev Ahmad (Elsevier, 2022)
Multidisciplinary care in healthcare is becoming the preferred approach to optimizing outcome. We present a case in which a patient developed a thrombotic occlusion of the mid left anterior descending coronary artery (very late stent thrombosis) leading to acute myocardial infarction while presenting for a dental extraction. Prior to the dental extraction his antiplatelet medication was held to minimize his risk of bleeding. This raises a question regarding the optimal use of antiplatelet medication during dental procedures. In complex cardiac patients we propose a multidisciplinary approach to antiplatelet management during the periprocedural period.